2017
DOI: 10.3390/met7020052
|View full text |Cite
|
Sign up to set email alerts
|

XPS and AFM Investigations of Ti-Al-N Coatings Fabricated Using DC Magnetron Sputtering at Various Nitrogen Flow Rates and Deposition Temperatures

Abstract: Ti-Al-N coatings were deposited by direct current magnetron sputtering (DCMS) onto IN 718 at different nitrogen flow rates and deposition temperatures. The coatings' properties were characterized using atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS) as well as nanoindentation. It was found that higher deposition temperature leads to higher surface roughness and nitrogen flux influences the shape of grains. According to XPS, the bonding structure of all coatings exhibited the (Ti,Al)N phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…This is confirmed by the results from Obrosov et al [10], which show a surface roughness ms of 13.0 nm for AlTiN coatings deposited by dcMS at the same average power and nitrogen flow rate. According to Figure 14 (100 Hz), the surface is characterized by many elevated, rounded particle-like structures with various lateral dimensions (red marked), which may result from different velocities of coating growth or from the deposition of droplets caused by arcs.…”
Section: Surface Roughness and Topographysupporting
confidence: 81%
See 4 more Smart Citations
“…This is confirmed by the results from Obrosov et al [10], which show a surface roughness ms of 13.0 nm for AlTiN coatings deposited by dcMS at the same average power and nitrogen flow rate. According to Figure 14 (100 Hz), the surface is characterized by many elevated, rounded particle-like structures with various lateral dimensions (red marked), which may result from different velocities of coating growth or from the deposition of droplets caused by arcs.…”
Section: Surface Roughness and Topographysupporting
confidence: 81%
“…So, AlTiN coatings deposited by HPPMS generally show a denser and smoother structure without column growth than coatings deposited by dcMS at the same average power due to increased metal ion bombardment [15]. This is confirmed by comparing the coating structure with published results from Obrosov et al [10]. Such a dense featureless, feathery coating structure is typical for coatings deposited with pulsed magnetron sputtering as, for example, Keunecke et al [48] and Jílek Jr. et al [49] have shown.…”
Section: Grain Sizes and Coatingsupporting
confidence: 77%
See 3 more Smart Citations